The Net Promoter Score in low-cost fitness centres: A comparative analysis according to gender, business and autonomous communities - Jiménez Jiménez, Pablo; Vidal Vilaplana, Alberto; Nuñez-Sánchez, José M.; Gregori Faus, Cristian (SPORT TK-EuroAmerican Journal of Sport Sciences, 2024)
The Net Promoter Score (NPS) has been recently validated as a reliable instrument for measuring loyalty among users of Low-Cost fitness centres. However, the number of studies that have tested its validity to discriminate and show differences between centres, chains or other socio-demographic variables is still limited. For this reason, the present research was carried out with the aim of analysing whether there are differences in the NPS score between different sociodemographic variables. For this study, a survey was carried out by means of an on-line questionnaire to a total of 3,832 users of 47 Low-Cost sports centres. The instrument used was composed of the subjective loyalty item Net Promoter Score, as well as several sociodemographic questions of interest. The questionnaire responses were collected and analysed using JASP software for inferential analysis. According to the results, significant differences were found according to the sex of the users, the company distributing the service and the autonomous community where the centres were located. Future research should analyse possible differences in the NPS score according to other socio-demographic variables such as members longevity or frequency of use.